Human impact on the Cape of Good Hope Nature Reserve - Benkenstein, Howard (Department of Environmental and Geographical Science, 2016)
The problem investigated in this study is the environmental effect of outdoor recreation on a valuable conservation area, the Cape of Good Hope nature reserve. The approach adopted views the reserve as a business concern that produces service commodities from the resources of the natural environment. Supply of these commodities was estimated from a visitor activity profile obtained by combining traffic count data with timed observations on visitor behaviour. Demand was assessed from the results of a visitor survey and from information obtained from a literature review. The results of these investigations provided a data base for formulating a business management policy for the reserve. The findings of the study were that the shortage of open space in Cape Town and the Western Cape is a human ecological problem and that a business management policy which reinforces human behavioural links with the environment would be both an economic solution and an eco- logical solution to the current controversy surrounding matters related to conservation in the Cape of Good Hope nature reserve.